Problems faced by non-English department students of Nahdlatul Ulama University of Blitar in learning English - Tyas Alhim Mubarok; Siti Rofiah (Politeknik Negeri Bali, 2022)
English is not only considered as obligation course but also it is now a need course. Therefore all university students including non-English department must have English course to prepare themselves facing globalization and industrial era. As the result, it is salient to know what problems they are facing in learning English. So the lecturers are expected to be able to improve their ability in achieving the goals in learning English. This study is aimed to investigate what kinds of problem faced by non-English department students in learning English. This study belongs to descriptive quantitative research method. The data were gained by observing and giving questionnaire to the non-English department students. The result shows that non-English department students mostly find difficulties in almost English skills such as speaking, reading, writing, and listening. Therefore it is needed more efforts for lecturers to teach non-English department students well by selecting the appropriate teaching methods.